Dạy học hát cho sinh viên ngành Giáo dục mầm non Trường Đại học Hoa Lư hướng tới trường học hạnh phúc - Hoàng Thị Hường, Hoàng Thị Hường; Đỗ Thị Thanh Nhàn, Đỗ Thị Thanh Nhàn (Tạp chí Giáo dục, 2026)
In the context of current educational reform, building a happy learning environment is regarded as an important goal for fostering learners’ holistic development. For students majoring in Early Childhood Education in general, and those at Hoa Lu University in particular, such an environment not only contributes to the development of professional competencies but also nurtures positive emotions and a love for the teaching profession. However, the practice of teaching singing at Hoa Lu University still reveals several limitations, such as learning spaces and teaching methods that have not fully promoted students’ interest or provided meaningful learning experiences, as well as a relatively low level of students’ activeness and initiative in learning activities. In response to this situation, the article proposes four measures for building a happy learning environment in teaching singing to Early Childhood Education students: innovating teaching methods, creating a friendly and emotionally supportive singing-learning space, strengthening communitybased musical activities linked to professional practice, and renewing assessment in a positive and humane direction. These measures contribute to improving learning effectiveness, fostering positive emotions, and cultivating a sense of happiness in learning among students.